THE EFFECT OF TEAM WORK, LEADERSHIP STYLE, AND ORGANIZATIONAL CULTURE ON NURSE PERFORMANCE WITH ORGANIZATIONAL COMMITMENTS AS MEDIATION VARIABLES IN HOSPITAL TYPE B IN JAKARTA - Wahyuningsih, Sri Ari; Thoyib, Armanu; -, Rofiaty; Sabil, Ananda (Accounting Department,, 2019)
ABSTRACT This study aims to analyze the influence of team work, leadership style and organizational culture on nurse performance with organizational commitment as a mediating variable. The research unit is nurses at Type B hospitals in Jakarta. The population is 1362 nurses. Methods of collecting data using surveys. The research instrument used a questionnaire. Questionnaires were distributed to 523 respondents. Data analysis method uses Structural Equation Modeling-Partial Least Square SEM-PLS). The results of the study prove that teamwork has a positive effect on nurse performance. Teamwork does not affect organizational commitment. Organizational culture has a positive effect on nurse performance. Organizational culture has a positive effect on organizational commitment. Leadership style does not affect nurse performance. Leadership style does not affect organizational commitment. Organizational commitment has a positive effect on nurse performance. Organizational commitment cannot play a role in mediating the influence of teamwork on nurse performance. Organizational commitment can play a role in mediating the influence of organizational culture on nurse performance. Organizational commitment cannot play a role in mediating the influence of leadership style on nurse performance.Â Keywords: Teamwork, Organizational Culture, Leadership Style, Organizational Commitment, Nurse Performance.